Research on Low-temperature Phase Change Cool Storage System during the Melting Process - 吴碧容; 童明伟; 李兴仁 (Zhileng xuebao)
Heat-transfer characteristics during melting of KCl-H_2O were determined for internal ice-on-coil cool storage system.The effects of coolant inlet temperature on the heat-transfer characteristics were primarily analyzed.Heat transfer from tube to the phase change material is strongly influenced by natural convection of melted PCM after the comparison of the values between experiment and calculation based on conduction.The amounts of cool discharging were correlated with the dimensionless groups of Fo,Ste,and Re.